THE CULTURAL VALUES OF BATAK TOBA IN BATU GANTUNG LOCAL TRADITION IN SAMOSIR ISLAND - Pani Gultom; Muhammad Natsir; Fauziah Khairani Lubis (LINGUISTICA, 2020)
The research was found on the topic about  The Cultural Values of batak Toba in Batu Gantung Local Tradition in Samosir Island. This study was conducted by applying descriptive qualitative method. The source of data was taken from the informants who live around Samosir Island, Kabupaten Simalungun. The technique for analyzing the data is descriptive qualitative research based on The Cultural Values in Sibarani (2013). The result of this research was The Cultural Values of Batak Toba in Batu Gantung Local Tradition in Samosir Island are Seeing Each Other Frequently, Honesty (30%), courtesy, social solidarity, harmony and conflict resolution (60%), welfare, hard work, discipline, mutual cooperation, gender management (80%) and education, health, cultural preservation and creativity, environmental concern, peace, commitment, positive thoughts, and gratitude. (100%). Keywords: Cultural Values, Local Tradition